Lenguaje y grupos sociales. Algunas observaciones sobre el programa intencional en ontología social. - Paolicchi, Leandro (Revista Estudios de Filosofía)
The following paper examines Tuomela's explanation of the appearance of basic social facts. In this proposal, the elementary components of a social ontology are due to the "collective intentionality" shared by different actors. Even though Tuomela alludes to language being present in some forms of intentionality in his exhibition, his reconstruction is oriented towards other forms of generating social facts that supposedly would not include it. In this writing, it will be argued, on the contrary, that it is not possible to avoid the main mechanism of generation of basic phenomena of sociality in any of its instances. Once language takes its central place as the main mechanism for coordinating action, creator of social groups and guide for a social ontology, many of the distinctions of the intentionalist program lose relevance from an ontological point of view.